ANTIOXIDANT AND TOXICITY ACTIVITIES of Gracilaria gracilis METHANOL EXTRACT BASED ON DIFFERENT EXTRACTION METHODS - Riong Seulina Panjaitan; Windri Yuliana (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
Gracilaria gracilis (red macroalgae) was collected from Sayang Heulang Beach, Garut, West Java. It has a number of secondary metabolites that potentially serve as a source of natural antioxidants. The objective of this study was to compare the optimal extraction method in particular time variation for producing the highest percent of yield, antioxidant activity, and toxicity of G. gracilis methanol extract. This study was conducted experimentally, including macroalgae sampling and preparation, phytochemical screening, extraction of G. gracilis by maceration and UAE methods, antioxidant activity testing based on the DPPH test (2.2 diphenyl-1-picrylhydrazyl) and toxicity testing using the BSLT (Brine Shrimp Lethality) method. The results indicated that the methanol extract of G. gracilis contains flavonoids and steroids, with yield percentages of 12.93% for maceration and 12.1% for UAE. The antioxidant activity (IC50) of maceration was 86.46 ppm, whereas the UAE was 59.01 ppm. Then, the toxicity test (LC50) for maceration was 28.35 ppm whereas the UAE was 27.76 ppm. Macerated methanol extract and UAE G. gracilis have the potential to be powerful antioxidants based on their IC50 values. Then, macerated methanol extract and UAE are included in the highly toxic category.